Report sections in English magazines: an alternative reading media for the English improvement - Bambang Suryanto (Jurnal Linguistik Terapan, 2011)
One of the factors that can boost the students’ vocabulary expansion of English rapidly is reading. As the students are limited to reading texts provided in their daily English class, they may find it is boring to read English passages. They can get maximum benefit from their reading, the teacher may encourage the students to choose for themselves what they read and to do so for pleasure and general language improvement (Harmer: 2007). It would be a good idea if they are introduced to more varied genres of reading text, say, English newspaper and magazines. Besides these texts provide more up‐to‐date discourse, they are also easily obtained. Moreover, newspapers and magazines are authentic in terms that they are not simplified reading texts as the students find in the classroom. With an extensive activity of reading these kinds of materials they are trained to cope with the same kinds of reading that are encountered by native speakers of the target language (Ur: 1996).